Estructura reglamentaria de la agencia para la defensa jurídica y patrimonial del Estado en Colombia (2014)
The role of the Agency for the Legal and Patrimo-nial Defense of the State has not been fully regu-lated in Colombia, despite being crucial, because decentralized and national instances have missed this event. Institutional analysis provides elements to articulate the claims of the agency with the orga-nizational capacity of the Colombian State to meet this challenge. The State should assess its purposes and functions according to the claims of the agency. Incidentally, institutional analysis opens in the State structure the opportunity to consolidate the para-meters of the agency, to finally print on the accou-ntability framework of the State such leeway. The State must include legal defense, but without ne-glecting their commitments